Analysis on switching cost versus bundling price under consumer adoption for choosing smart TV over pay TV - Ahreum Hong; Eun Yu; Junseok Hwang (International Telecommunications Society (ITS), 2014)
The emergence of smart TV device encourages the reconsideration of the customer's subscription on the pay TV so that the phenomenon of cord-cutting evokes the other dimension of MVPD (Multi-Channel Video Programming Distribution) industry itself. Two major paths to adopt the new platform in MVPD market cover the switching cost and effect for the new platform such as smart TV and restrain the discount price by bundling triple-play which is one provision over a single broadband connection of two bandwidth-intensive services such as high-speed Internet access and television, and the latency-sensitive telephone. The research question over this simultaneous equation model exhibits that rate of customer subscription affects with more attention from demand-pull phenomenon by the high switching cost versus bundling price for multiple play service in behavioral economics way. Behavioral economics can explain the way of consumer's choice by providing it with more realistic psychological foundations. The hypothesis investigates the incentive mechanism has positive effect from the discount rate by tying the product bundling within MVPD service provision. Shapiro and Varian (1998) examine some of the business strategy implications of switching costs at a lay reader level. The switching cost results in the lock-in effect and takes scale economies of demand side. Farrell and Shapiro (1989) mention that once they are locked in, they can be a substantial source of profit whether it is substation or not. Also customer left the current service due to that cost. The prerequisite for switching cost investigate the product complexity (Gatignon and Robertson, 1992; Klemperer, 1995), heterogeneity of supplier in market (Schmalensee, 1982), the product diversity from the supplier side (Blattberg and Deighton, 1996; Klemperer, 1995; Ram and Jung, 1990), the level of modification in consideration of customer demand (Bhardawaj et al., 1993), the experience of alternatives (Bhattachary et al., 1995), the experience of switching choice (Bhattacharya et al.,1995; Nilssen, 1992), and time limitation of selection pressure or individual characteristic of risk aversion could be the factor to reorganization of switching cost by customer. Previous literature tries to explore the path and find out the factors which effect on the customer's switching behavior.
Keywords: L22; L82; 330; Pay TV market; Switching cost; Bundling price; Smart TV; Simultaneous Equation Modeling